Alternative access in high-risk patients in the era of transfemoral aortic valve replacement. Issue 6 (1st August 2022) - Zubarevich, Alina; Szczechowicz, Marcin; Jánosi, Rolf-Alexander; Lind, Alexander; Rassaf, Tienush; Malik, Rizwan; Thielmann, Matthias; Schmack, Bastian; Kamler, Markus; Ruhparwar, Arjang; Weymann, Alexander; Wendt, Daniel
Abstract: Background: We aimed to evaluate the outcomes of transapical and transaortic transcatheter aortic valve replacement (TAVR) in high-risk patients who were not suitable for transfemoral access and had a logistic EuroSCORE- I  ≥ 25% and Society of Thoracic Surgeons (STS) score >6%. 'STS/ACC TAVR In-Hospital Mortality Risk App' was evaluated. Material and methods: Between January 2016 and May 2020, 126 patients at very high risk for aortic valve replacement underwent transapical ( n  = 121) or transaortic ( n  = 5) transcatheter aortic valve replacement. TAVR was performed using SAPIEN 3™ or ACURATE TA™ prosthesis. Results: The logistic EuroSCORE-I was 40.6 ± 14.0%, the STS-score 7.9 ± 4.6%, and STS/ACC-score 8.4 ± 3.4%. Valve implantation was successful in all patients. Operative, in-hospital and 30-days mortality, were 0, 7.9, and 13.5%, respectively. Survival was 72% at one year and 48% at four years. Expected/observed in-hospital mortality was 1.0 for the STS-score and 1.06 for the STS/ACC-score. Renal failure, low ejection fraction, and postoperative acute kidney injury, hemorrhage, and vascular complications were identified as independent predictors for 30-day mortality. Conclusions: Transapical and transaortic TAVR in high-risk patients unsuitable for transfemoral access is still a reasonable alternative in these patients. STS and STS/ACC-score appear to be highly accurate in predicting in-hospital mortality in high-risk patients undergoing TAVR.